Deep Sequencing Reveals the Effect of MeJA on Scutellarin Biosynthesis in Erigeron breviscapus. - Rui-Bing Chen; Jiang-Hua Liu; Ying Xiao; Feng Zhang; Jun-feng Chen; Qian Ji; He-Xin Tan; Xin Huang; Hao Feng; Bao-Kang Huang; Wan-Sheng Chen; Lei Zhang (PLoS ONE, 2015)
Background Erigeron breviscapus, a well-known traditional Chinese medicinal herb, is broadly used in the treatment of cerebrovascular disease. Scutellarin, a kind of flavonoids, is considered as the material base of the pharmaceutical activities in E. breviscapus. The stable and high content of scutellarin is critical for the quality and efficiency of E. breviscapus in the clinical use. Therefore, understanding the molecular mechanism of scutellarin biosynthesis is crucial for metabolic engineering to increase the content of the active compound. However, there is virtually no study available yet concerning the genetic research of scutellarin biosynthesis in E. breviscapus. Results Using Illumina sequencing technology, we obtained over three billion bases of high-quality sequence data and conducted de novo assembly and annotation without prior genome information. A total of 182,527 unigenes (mean length = 738 bp) were found. 63,059 unigenes were functionally annotated with a cut-off E-value of 10(-5). Next, a total of 238 (200 up-regulated and 38 down-regulated genes) and 513 (375 up-regulated and 138 down-regulated genes) differentially expressed genes were identified at different time points after methyl jasmonate (MeJA) treatment, which fell into categories of 'metabolic process' and 'cellular process' using GO database, suggesting that MeJA-induced activities of signal pathway in plant mainly led to re-programming of metabolism and cell activity. In addition, 13 predicted genes that might participate in the metabolism of flavonoids were found by two co-expression analyses in E. breviscapus. Conclusions Our study is the first to provide a transcriptome sequence resource for E. breviscapus plants after MeJA treatment and it reveals transcriptome re-programming upon elicitation. As the result, several putative unknown genes involved in the metabolism of flavonoids were predicted. These data provide a valuable resource for the genetic and genomic studies of special flavonoids metabolism and further metabolic engineering in E. breviscapus.